2011
DOI: 10.1016/j.actbio.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of titania-based surface modification of polyethylene terephthalate on bone–implant bonding and peri-implant tissue reaction

Abstract: Organic polymers can be uniformly surface-modified with bioactive TiO(2) by using a sol-gel method. Titania-based surface-modified polyethylene terephthalate (TiPET) plates and fabric have shown apatite-forming ability in simulated body fluid. Here, we first investigated the bone-bonding ability and mechanical bonding strength between the surface-modified layer and the base material (PET) of TiPET plates in vivo. For clinical applicability, we also examined the bone-bonding ability of TiPET fabric and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This method could enhance the adhesion of osteoblastic cells in vitro [9][10][11]. In a different study, Saito et al demonstrated that titania-based surfacemodified PET can be successfully exploited in vivo as flexible bone substitutes, bioactive artificial ligaments, and suture threads [12]. Other surface modifications, such as the covalent binding of RGD containing peptides [13,14], surface bi-functionalization with both induction (BMP-2, 7 or 9) and adhesion (GRGDSPC)…”
Section: Introductionmentioning
confidence: 99%
“…This method could enhance the adhesion of osteoblastic cells in vitro [9][10][11]. In a different study, Saito et al demonstrated that titania-based surfacemodified PET can be successfully exploited in vivo as flexible bone substitutes, bioactive artificial ligaments, and suture threads [12]. Other surface modifications, such as the covalent binding of RGD containing peptides [13,14], surface bi-functionalization with both induction (BMP-2, 7 or 9) and adhesion (GRGDSPC)…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the properties evaluated in this study, TiO 2 demonstrated bioactivity when incorporated in polymers (Saito et al 2011;Shimizu et al 2016). The evaluation of the possible biomimetic remineralization promoted by the synthesized TiO 2QDs/BMI.BF4 should be assessed since its sizes present compatible dimensions with the intrafibrillar spaces of collagen (Bertassoni et al 2012).…”
Section: Discussionmentioning
confidence: 87%
“…Saito et al. [ 107 ] attained titania coating by sol–gel method and investigated the effect of titania-based surface modification of PET on bone-implant bonding and peri-implant tissue reaction. According to the test results, the bone-bonding ability was effectively achieved in PET materials by titania-based surface modification, owing to obvious HAP deposition induced by titania coating.…”
Section: Manufacturing Technologies For Artificial Ligament Bioactivi...mentioning
confidence: 99%